Estudo da lixiviação em desenvolvimento no concreto da eclusa 1, estrutura componente do sistema de transposição da barragem de Tucuruí - OLIVEIRA, Thais Valadares (2022)
Concrete is the construction material most used worldwide and main constituent of important developments, as in the case of large dams. This justifies the concern to know the behavior of this material, in order to maintain the integrity and safety of these structures. Several mechanisms are able to lead to the deterioration of concrete elements, be them based on chemical or physical processes. Leaching is one of these. Through it the concrete undergoes, in time, to a significantly reduce in resistance and increase in permeability, mainly due to mass loss caused by it. Leaching leads, through chemical processes, hydrolysis of the cement paste components due to percolation of pure or acidic waters, promoting the carrying of essential substances. This sort of deterioration was identified in broad development in the Lock 1, component structure of the System of Unevenness Transposition of Tucuruí Dam and analyzed by quantification of the massive mass loss during the study period (twelve months) and estimated the consequential reducing in resistance and increasing in the porosity of the concrete. Moreover, some pathologies identified during the study were also analyzed, such as carbonation and surface wear of the dam vestment in order to verify possible correlations with the pathology focus of this work. The leaching product is a white crust, also known in the literature as efflorescence, which is formed due to contact between the material leached of concrete and carbon dioxide suspended in atmospheric air. For the measurement of the mass loss in the period, were related the flows in drains where it was observed higher incidence of the pathology and the differences between the concentrations of the substances found in chemical analyzes of the water coming out of them and of the one in reservoir of the dam. The estimated loss of resistance was possible through both non-destructive test, in this case was used sclerometry, and even through destructive testing, comprising extraction and rupture of specimens from the concrete of the vestment upstream face of the Lock. Verification of the increase in porosity, in turn, had the aid of both images taken with a Scanning Electron Microscope (SEM) and laboratory tests used for the discovery of the void ratio and the absorption rate of the extracted specimens. The carbonation was measured with the support of phenolphthalein solution and caliper and surface wear was measured empirically from the comparison between the specimens taken below the maximum water level (height 74 m) and above it (used as reference). Indeed, the substance that had more significant value between the extracted from concrete is calcium, which justifies the intense generation in the output of the drains of calcium carbonate (efflorescence), as well as the loss of strength due to the removal of cement products responsible for the conference of its resistance and, of course, the increased of porosity, since there was a change in microstructure of the material, which had part of their substances carried by the action of intense water percolation. It was also observed occurrence of carbonation throughout the vestment and a widespread and uniform surface wear below the maximum water level.